2021
DOI: 10.7150/ijms.45980
|View full text |Cite
|
Sign up to set email alerts
|

Altered intestinal microflora and barrier injury in severe acute pancreatitis can be changed by zinc

Abstract: To investigate the effect of zinc (Zn) supplementation on intestinal microflora changes and bacterial translocation in rats with severe acute pancreatitis (SAP), the rats were divided into the sham surgery (SS), SAP, SS + Zn, and SAP + Zn groups. Saline (0.1 mL/100g) and 5% sodium taurocholate were injected into the pancreaticobiliary duct of the rats in the SS and SAP + Zn groups, respectively. Intraperitoneal injection of 5 mg/kg Zn was performed immediately after injecting saline or 5% sodium taurocholate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It was found that intestinal dilatation, epithelial cell shedding, and inflammatory infiltration occurred at 12 h in SAP rats. The severity of SAP patients is closely related to intestinal mucosa permeability ( 12 , 39 ), and intestinal mucosal permeability is commonly known as the most direct and accurate element that reflects intestinal mucosal barrier function ( 40 , 41 ). D-lactate, which is a kind of the intestinal metabolite, enters the blood circulation and significantly increases when the intestinal mucosal barrier function is seriously damaged ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that intestinal dilatation, epithelial cell shedding, and inflammatory infiltration occurred at 12 h in SAP rats. The severity of SAP patients is closely related to intestinal mucosa permeability ( 12 , 39 ), and intestinal mucosal permeability is commonly known as the most direct and accurate element that reflects intestinal mucosal barrier function ( 40 , 41 ). D-lactate, which is a kind of the intestinal metabolite, enters the blood circulation and significantly increases when the intestinal mucosal barrier function is seriously damaged ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the intestinal sections were stained with 3,3′-diaminobenzidine (DAB) and hematoxylin. Both HE staining and IHC staining were performed according to the method of Su and Tang [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, Zn sulfate supplementation in rats with pancreatitis significantly reduced endotoxic accumulation (LPS) and tissue IL-1β and TNFα expression, as well as attenuated pancreatitis-associated gut permeability and bacterial translocation to pancreas, liver, and mesenterial lymph nodes. The impact of Zn on gut microflora biodiversity was characterized by a reduction in Escherichia numbers, and an elevation of Bifidobacterium and Lactobacillus gene copy numbers in caecum [ 74 ]. Correspondingly, in patients with chronic pancreatitis characterized by high incidence (~40%) of small intestinal bacterial overgrowth, the latter was characterized by a significant negative correlation with serum Zn levels [ 75 ].…”
Section: Extraintestinal Effects In Models Of Human Diseasesmentioning
confidence: 99%